Coleta seletiva: análise dos sistemas Porta a Porta e P.E.V.: um estudo de caso nos municípios de Londrina e Caxias do Sul - Tamiozo, Matheus Higino (2015)
With the progress in current society, the management of solid wastes is one of the greatest challenges. The solid wastes process is one of the alternatives to reduce the incidence of materials that can be reused, both by industry and by population, avoiding the overload on the landfills. The National Policy (Law no.12.305/2010) obligates the insertion of recyclers, this way, more professionals are receiving wage and moving the economy. This study is aimed to analyze the selective collection system implemented in Londrina with the inclusion of pickers in the recycling process. To achieve the goal, the main authors related to the theme were raised: ways of selective recycling process and integration of collectors in the recycling process and the methodology involved the use of a questionnaire and a national database information system of the sanitation and with main results, it was possible to see there was a difference between the mechanized collection system with P.E.V. in Caxias do Sul with the manual collection system, the Door to Door in Londrina checking the main differences in social issues, environmental and economic.